Stretching The Boundaries Of Equity: Mahadevan & Anor V. Manilal & Sons (M) Sdn. Bhd. - Ahmad, Sharifah Suhana (Journal of Malaysian and Comparative Law, 2019)
Results of application of Torrens System to land law in Malaysia, examined in light of Mahadevan & Anor V. Manilal & Sons (M) Sdn. Bhd.